Evaluation of in vitro digestion methods and starch structure components as determinants for predicting the glycemic index of rice - Pautong, Putlih Adzra; Añonuevo, Joanne Jerenice; Guzmán, Maria Krishna de; Sumayao, Rodolfo; Henry, Christiani Jeyakumar; Sreenivasulu, Nese (Elsevier, 2022)
Mainstreaming the low glycemic index (GI) trait in breeding programs is constrained by low-throughput and high-cost clinical GI phenotyping. This study aimed to evaluate the potential of starch fine structure components and simulated digestion parameters in predicting GI in rice. Amylose (AM1 and AM2; r = −0.94 and r = −0.80, respectively, p < .05) and amylopectin fine structure (MCAP, SCAP, and SCAP1; r = 0.78-0.86, p < .05) measured through size-exclusion chromatography along with resistant starch (r = −0.81, p < .05) in seven (7) rice accessions showed high correlation with in vivo GI. Meanwhile, starch hydrolysis extent (SH) and the corresponding area under the digestion curve (AUC) obtained through in vitro digestion were found to be of higher correlation with GI, even within shorter digestion periods of 5 min or 30 min (r = 0.96, p < .01). These results highlight the potential use of these parameters as predictors of GI, with improved predictive capacity through a multiple regression model. Higher correlations of simulated digestion AUC with GI may be due to its ability to account for the overall food matrix native macro- and micro-structures, gaining an added advantage over SEC method as a predictive tool in studying rice GI variability. Validation in a larger population is an inevitable next step.